Every day the war continues in my body: examining the marked body in postconflict northern Uganda - Hollander, Theo (International journal of transitional justice, 2014)
Human bodies have assumed centre stage in modern warfare, and few armed conflicts epitomize this more than the war in northern Uganda, where both rebel groups and government forces violated bodily integrity and altered human tissue to communicate messages, humiliate the enemy and their support base, and dominate both people and territory. The injuries and disabilities inflicted during wartime continue to affect people long after the conflict has come to an end. People whose bodies were ‘marked’ continue to embody the war in everyday activities in terms of pain, disabilities and loss of mobility. In other words, the war continues in their bodies. Most marked bodies struggle to conform gender performances to expectations. Furthermore, a decline in the productivity of people with marked bodies and failure to reciprocate mutual beneficial interaction leads to ruptures within social capital networks, resulting in widespread stigmatization and discrimination. Yet, focus on the body seems to be largely missing in peace processes and transitional justice. In the aftermath of armed conflict, where so many bodies have been marked, disability mainstreaming should become a quintessential element in transitional justice. This goes beyond medical interventions, meaning that in all transitional justice thinking and practice, attention is paid to how marked bodies can be included, participate and benefit. To ensure inclusion of marked bodies and other victim groups, more micro-analysis is needed that distinguishes survivor groups in terms of their day-to-day survival concerns, challenges, experiences, needs and aspirations.